1960
DOI: 10.1002/ange.19600722205
|View full text |Cite
|
Sign up to set email alerts
|

Synthesen in der Vitamin‐A‐Reihe

Abstract: milienlg~ 20). Ob die bei Gangliosid-Speicherkrankheiten auftretenden Ganglioside identisch sind mit denjenigen, die wir bisher am Rinderhirn kennen, weiB man nicht.Die letzte Frage ware, wieweit Untersuchungen der angedeuteten Art iiberhaupt dazu beitragen konnen, elektrophysiologische und sinnesphysiologische Erscheinungen besser zu verstehen. Auf diese Frage ware folgende Antwort zu geben: Man stelle sich vor, daB es irgendwo in der Welt Chemiker gabe, die noch nie von einem Magnetophonband etwas erfahren h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

1966
1966
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(20 citation statements)
references
References 13 publications
0
18
0
2
Order By: Relevance
“…According to [21], [56], if the base does not contain lithium, the ylide is said to be prepared under salt-free conditions. It became apparent that most triphenylphosphonium salts with a negative charge on the a-carbon atom react even with weaker bases than phenyllithium, yielding the corresponding ylides, usually in good yields [57], [58]. Suitable proton acceptors include alkali metal alkoxides and sodium amide [57], [59].…”
Section: Usesmentioning
confidence: 99%
“…According to [21], [56], if the base does not contain lithium, the ylide is said to be prepared under salt-free conditions. It became apparent that most triphenylphosphonium salts with a negative charge on the a-carbon atom react even with weaker bases than phenyllithium, yielding the corresponding ylides, usually in good yields [57], [58]. Suitable proton acceptors include alkali metal alkoxides and sodium amide [57], [59].…”
Section: Usesmentioning
confidence: 99%
“…We have found that cobinamide (2) or vitamin BIZ obtained from fermentation mixtures can also be converted into cobyric acid.…”
Section: Conversion Of Cobinamide Into Cobyric Acidmentioning
confidence: 99%
“…We have now found that interconversion of the diastereoisomeric betaine ylides (2) [31 is extremely rapid [4J. These ylides are formed if the betaine-LiX adduct ( I ) is treated with phenyl-lithium or n-butyl-lithium in ether/tetrahydrofuran (1 : 1) at -30 "C, and with proton donors (e.g., hydrogen chloride or t-butyl alcohol) they regenerate the betaine-LiX adducts ( I ) .…”
Section: Trans-selective Olefin Synthesesmentioning
confidence: 99%
“…The important manufacture of BASF (the Badische Anilin and Sodafabrik) (18), is based an Wittig's elegant olefin synthesis which revolutionized the whole polyene chemistry. In 1964 c 15 -vinyl-ß-ionol was directly transformed to vitamin A acetate (56).…”
Section: The Manufacture Of Vitamin a (44)mentioning
confidence: 99%
“…BASF condenses C 5 -~~nyl-ß-ionol in a Wittig reaction with a c 5 -aldehyde directly to vitamin A acetate 1 (56). This important Wittig reaction c 15 + c 5 was developed by Pommer (18,56,57) as shown in Fig. 11: c 15 -vinyl-ß-ionol an treatment with triphenylpho~phoniumhalide gives the c 15 -wittig salt which is also a building stone in BASF's manufacture of ß-carotene and c~tranaxanthin.…”
Section: The Manufacture Of Vitamin a (44)mentioning
confidence: 99%